2022
DOI: 10.1128/spectrum.00622-22
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Asymptomatic Transmission of SARS-CoV-2 in K-12 Schools, British Columbia, Canada April to June 2021

Abstract: There is concern that schools may be a setting where asymptomatic infections might result in significant “silent” transmission of SARS-CoV-2, particularly after the emergence of more transmissible variants of concern. After the programmatic implementation of a strategy of asymptomatic testing of close COVID-19 contacts as part of contact tracing in the school setting, the majority of the secondary cases were still found to have occurred in home or social contacts.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Thus, it is important to provide tangible evidence to support or refute public claims. Despite frequent COVID-19 exposures in schools the data here support that many school COVID-19 cases were acquired outside, rather than within the school setting 8 27 28…”
Section: Discussionsupporting
confidence: 55%
“…Thus, it is important to provide tangible evidence to support or refute public claims. Despite frequent COVID-19 exposures in schools the data here support that many school COVID-19 cases were acquired outside, rather than within the school setting 8 27 28…”
Section: Discussionsupporting
confidence: 55%
“…At the start of the pandemic, children were rarely infected, and if they were infected, they had a lower transmissibility than adults [18]. Previous studies have revealed that little transmission has taken place in schools during the pandemic [18,19]. During our study period schools mostly used precautionary measures such as quarantine and homeschooling.…”
Section: Principal Findingsmentioning
confidence: 90%
“…These results are also in keeping with other seroprevalence and contact tracing studies conducted in BC school settings that showed low rates of SARS-CoV-2 transmission. [15][16][17][18][19] We demonstrated a higher seropositivity among infants and young adults compared with schoolaged children. Our findings contrast with other cohorts in which seropositivity has been reported.…”
Section: Anti-s Igg Concentrationsmentioning
confidence: 60%
“…The copyright holder for this preprint this version posted August 18, 2023. ; https://doi.org/10.1101/2023.08.13.23294036 doi: medRxiv preprint Enrollment for each phase was based on five, 5-year age brackets (0-4, 5-9, 10-14, [15][16][17][18][19][20][21][22][23][24]. There was a target sample size of 500 participants per 5-year age group, per phase; each phase was completed when target sample size was reached.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%